2022
DOI: 10.1186/s41155-022-00211-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the psychodynamic functioning of patients with PTSD and CPTSD: qualitative analysis from the OPD 2 interview

Abstract: The traumatic event produces intolerable excitations to the psychic apparatus that searches to relief them through the production of symptoms. When established, patients with post-traumatic stress disorders (PTSD) and complex post-traumatic stress disorder (CPTSD) may experience flashbacks, somatizations, negative emotions about themselves, and difficulty in social contact. This work seeks to understand how the psychodynamic functioning of women victims of interpersonal and urban violence, diagnosed with these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…felt as a threat, a negligence, with the occurrence of withdrawal. Such characteristics confirm and strengthen what was identified by Both et al41 and Favaretto et al19 in studies on trauma patients.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…felt as a threat, a negligence, with the occurrence of withdrawal. Such characteristics confirm and strengthen what was identified by Both et al41 and Favaretto et al19 in studies on trauma patients.…”
supporting
confidence: 91%
“…In addition to ITE, patients revealed that they had experienced trauma prior to the event that caused PTSD, which supports different studies. 2,19,39 Trauma can become devastating, especially in childhood, as object representations become unstable, making it difficult to organize a sense of identity and the ability to reflect/mentalize. 40 The absence or fragility of the object's response to accept, interpret and satisfactorily respond to traumatic experiences, combined with the individual's responses to the experienced situation can lead to feelings of helplessness and abandonment, reactivated in other stressful situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Травматична подія викликає нестерпне збудження психічного апарату, який власне шукає їх полегшення за допо-могою створення невротичних симптомів. З точки зору операціоналізованої психодинамічної діагностики OPD-2 це може зумовлювати крихкість самопрезентації, домінування внутрішнього конфлікту за типом автономія/залежність або автаркія/турбота, зниження структурного рівня організації особистості до помірного або низького, порушення контролю імпульсів (Favaretto, Both, da Cruz Benetti & Freitas, 2022). В прикладному розумінні психодинамічні підходи в психотерапії травми працюють за рахунок підвищення рефлексивності, збільшення прояву зрілих захистів із супутнім зменшенням залежності від незрілих захисних механізмів психіки, інтерналізації більш безпечних моделей стосунків та відповідно покращення соціального функціонування загалом (Schottenbauer, Glass, Arnkoff & Gray, 2008).…”
Section: концептуальні підходи до розуміння феномену посттравматичног...unclassified
“…Considering that most adults with DESNOS also meet PTSD criteria [ 11 ], the latest edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [ 9 ] has included DESNOS psychopathology outcomes as specific features of PTSD. However, findings from clinical and research studies suggest that a PTSD diagnosis fails to adequately capture DESNOS’ constellation of symptoms [ 1 , 2 , 3 , 4 , 5 , 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] as PTSD emerges as a consequence of single-event traumas, or type I traumas [ 5 ], not directly attributed to another person’s abuse or neglect (e.g., natural disasters, vehicle accidents). PTSD psychopathology outcomes include intrusive memories, avoidance of the stimuli associated with the traumatic event, emotional numbing, arousal and emotional reactivity associated with the traumatic event [ 22 ].…”
Section: Introductionmentioning
confidence: 99%